Transmission of Bartonella henselae within Rhipicephalus sanguineus: Data on the Potential Vector Role of the Tick - Wechtaisong, Wittawat; Bonnet, Sarah I.; Lien, Yi-Yang; Chuang, Shih-Te; Tsai, Yi-Lun (PLoS neglected tropical diseases, 2020)
Bartonella henselae is a fastidious intraerythrocytic, gram-negative bacteria that causes cat scratch disease in humans. Ixodes ricinus has been confirmed to be a competent vector of B. henselae, and some indirect evidences from clinical cases and epidemiological studies also suggested that some other tick species, including Rhipicephalus sanguineus, may transmit the bacteria. B. henselae has been detected in R. sanguineus but no experimental investigations have been performed to evaluate the vector competency of this tick species regarding B. henselae transmission. To this end, this work aimed to assess the transstadial transmission of B. henselae between larvae and nymphs of R. sanguineus as well as transmission by nymphs infected at the larval stage. Four hundred B. henselae negative larvae were fed with B. henselae-infected blood by using an artificial membrane feeding system. After five days of feeding, B. henselae was detected by PCR in 57.1% (8/14) of engorged larval pools, 66.7% (4/6) of semi-engorged larval pools, and 66.7% (2/3) of larval feces pools. After molting, B. henselae DNA was also detected in 10% (1/10) of nymph pools, but not in tick feces. After a pre-fed step of nymphs infected at the larval stage on non-infected blood meal, B. henselae was detected by PCR in blood sample from the feeder, but no Bartonella colonies could be obtained from culture. These findings showed that B. henselae could be transstadial transmitted from R. sanguineus larvae to nymphs, and also suggest that these nymphs may retransmitted the bacteria through the saliva during their blood meal. This is the first study that validated the artificial membrane feeding system for maintaining R. sanguineus tick colony. It shows the possibility of transstadial transmission of B. henselae from R. sanguineus larvae to nymphs.